A minority of somatically mutated genes in pre‐existing fatty liver disease have prognostic importance in the development of NAFLD. (11th May 2022) - Mann, Jake P.; Hoare, Matthew
Abstract: Background: Understanding the genetics of liver disease has the potential to facilitate clinical risk stratification. We recently identified acquired somatic mutations in six genes and one lncRNA in pre‐existing fatty liver disease. We hypothesised that germline variation in these genes might be associated with the risk of developing steatosis and contribute to the prediction of disease severity. Methods: Genome‐wide association study (GWAS) summary statistics were extracted from seven studies (>1.7 million participants) for variants near ACVR2A, ALB, CIDEB, FOXO1, GPAM, NEAT1 and TNRC6B for: aminotransferases, liver fat, HbA1c, diagnosis of NAFLD, ARLD and cirrhosis. Findings were replicated using GWAS data from multiple independent cohorts. A phenome‐wide association study was performed to examine for related metabolic traits, using both common and rare variants, including gene‐burden testing. Results: There was no evidence of association between rare germline variants or SNPs near five genes ( ACVR2A, ALB, CIDEB, FOXO1 and TNRC6B ) and risk or severity of liver disease. Variants in GPAM (proxies for p.Ile43Val) were associated with liver fat ( p = 3.6 × 10 −13 ), ALT ( p = 2.8 × 10 −39 ) and serum lipid concentrations. Variants in NEAT1 demonstrated borderline significant associations with ALT ( p = 1.9 × 10 −11 ) and HbA1c, but not with liver fat, as well as influencing waist‐to‐hip ratio, adjusted for BMI. Conclusions: Despite the acquisition of somatic mutations at these loci during progressive fatty liver disease, we did not find associations between germline variation and markers of liver disease, except in GPAM. In the future, larger sample sizes may identify associations. Currently, germline polygenic risk scores will not capture data from genes affected by somatic mutations.